Dilwale dulhania le jayenge - Pandit, Lalit ca. 20./21. Jh; Pandit, Jatin ca. 20./21. Jh (Yash Raj Films, 2001)
Extras: Disc 1 - Movie. Disc 2 - Supplementary material: Theatrical trailer (Anamorphic with Dolby 4 track sound). A behind the scenes look at the making of the classics. Deleted scenes. An exclusive peek at the scenes that never made it to the theatres along with optional commentary by the director Aditya Chopra. Exclusive Interviews: Uday Chopra in conversation with Shah Rukh Khan, Kajol and Yash Chopra. Television Promos. Filmfare 1995 Highlights: Where "DDLJ" won an unprecedented 10 popular awards. The Success Story: A story featurette tracing the path of Dilwale Dulhania Le Jayenge. From its premiere to its becoming the longest running film of Indian cinema. DDLJ - THE 300 WEEKS CELEBRATION SPECIAL FEATURE. (from the container) ; en